PENGARUH STRUKTUR KEPEMILIKAN, LIKUIDITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2014)
The purpose of this study was to determine the variables that contribute to financial distress at the manufacturing company. Another aim is to conclusion the solution for the financial distress, relation to the variable-variable: institutional ownership, liquidity and leverage.This study uses secondary data obtained from Indonesia Stock Exchange (BEI). During period 2010 to 2011. Data used in this study include financial ratios and ownership structure ratio. The statistical methods used to test the hypothesis is logit model. The results of this study indicate that variable institutional ownership have a significant positif to financial distress, liquidity have a significant negative to financial distress, while leverage have no significant effect to financial distress